6. Using the identity (a + b)(a - b)=a*-b* find the following product:
(P+ 2)(p-2)
![using \: the \: identity(a + b)(a - b) = a ^{2} - b ^{2} \: find \: the \: following \: product using \: the \: identity(a + b)(a - b) = a ^{2} - b ^{2} \: find \: the \: following \: product](https://tex.z-dn.net/?f=using+%5C%3A+the+%5C%3A+identity%28a+%2B+b%29%28a+-+b%29+%3D+a++%5E%7B2%7D+-+b+%5E%7B2%7D+%5C%3A+find+%5C%3A+the+%5C%3A+following+%5C%3A+product)
Answers
Answered by
1
Answer:
p^2,-4
Step-by-step explanation:
(p+2) (p-2)
p^2-2^2
p^2-4
Similar questions